Functional and return to work outcomes following major trauma involving severe pelvic ring fracture. Issue 10 (30th May 2014) - Gabbe, Belinda J.; Hofstee, Dirk‐Jan; Esser, Max; Bucknill, Andrew; Russ, Matthias K.; Cameron, Peter A.; Handley, Christopher; de Steiger, Richard N.
Abstract Background There is limited evidence describing the long‐term outcomes of severe pelvic ring fractures. The aim of this study was to describe the longer term independent living and return to work outcomes following severe pelvic ring fracture. Methods Adult survivors to discharge from two major trauma centres with AO/Tile type B and C fractures were followed up at 6, 12 and 24‐months post‐injury to capture functional (Glasgow Outcome Scale‐Extended [GOS‐E]) and return to work data. Multivariable, mixed effects models were used to identify predictors of outcome. Results A total of 111 of 114 (97%) cases were followed up. The mean (SD) age of participants was 41.9 (18.9) years, 77% were male, 81% were transport‐related and 90% were multi‐trauma patients. Further, 11% were managed conservatively, 10% with external fixation and 79% with open reduction and internal fixation. At 24 months, 77% were living independently (GOS‐E > 4) and 59% had returned to work. Higher Injury Severity Scores (ISS) were associated with lower risk‐adjusted odds of return to work (P = 0.04) and independent living (P = 0.06). Post‐operative infection was associated with living independently (P = 0.02). Conclusion Despite the severity of the injuries sustained, 77% of severe pelvic ring fracture patients were living independently and 59% had returned to work, 2‐years post‐injury. Fracture type and management were not key predictors of outcome. Large‐scale multi‐centre studies are needed to fully understand the burden of severe pelvic ring fractures and to guide clinical management.